Scotland: Nation without Nationalism? - Ya. I. Maltsev (Сравнительная политика)
In the period before 1990s two concepts were used to describe the Scottish political development: “Nation without nationalism” and “The stateless nation”. After the devolution of 1998 and electoral achievements of SNP neither of these constructions can properly characterize the processes, undergoing in Scotland. The forming of new alignment of political powers in Scotland is not yet finished, but so far its development leads to the emergence of political configuration separated from that of All-British, with regard to extreme weakening of “big” parties in Scotland.